Race, School Discipline, and Magnet Schools - Karin Kitchens; NaLette Brodnax (SAGE Publishing, 2021)
School environment plays an important role in student outcomes. Increasingly, research has also highlighted the role school environment plays in the White-Black suspension gap. We test whether magnet schools reduce the White-Black suspension gap using data from Tulsa Public Schools. Using student-level and incident-level data from Tulsa, Oklahoma, we explore whether Black students receive exclusionary discipline at lower rates in magnet schools than in traditional schools compared with White students. Using matching techniques to minimize selection bias, we find that magnet schools in Tulsa are associated with a reduction in the racial suspension gap. In magnet schools in Tulsa, we do not find a racial gap in severity of incident or days assigned.